2016
DOI: 10.5194/angeo-34-399-2016
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of magnetotail fast flows and related magnetic disturbances

Abstract: Abstract. This study presents an investigation on the occurrence of fast flows in the magnetotail using the complete available data set of the THEMIS spacecraft for the years 2007 to 2015. The fast flow events (times of enhanced ion velocity) are detected through the use of a velocity criterion, therefore making the resulting database as large as almost 16 000 events. First, basic statistical findings concerning velocity distributions, occurrence rates, group structures are presented. Second, Superposed Epoch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 50 publications
2
20
0
1
Order By: Relevance
“…(1) is therefore reasonable. The TLS fit gives γ ≈ 1.493 ± 0.014, which is very close to the results of Baumjohann and Paschmann (1989), Zhu (1990), Goertz and Baumjohann (1991), and Borovsky et al (1998).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…(1) is therefore reasonable. The TLS fit gives γ ≈ 1.493 ± 0.014, which is very close to the results of Baumjohann and Paschmann (1989), Zhu (1990), Goertz and Baumjohann (1991), and Borovsky et al (1998).…”
Section: Resultssupporting
confidence: 83%
“…Earlier studies have already emphasized the necessity to group the data according to magnetospheric activity, usually using the AE index as a proxy (Baumjohann and Paschmann, 1989;Goertz and Baumjohann, 1991;Pang et al, 2015). Therefore, in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using superposed epoch analysis, Frühauff and Glassmeier (2016) recently showed the characteristics of fast flows and related magnetic disturbances in the magnetotail. They revealed that during the entire flow burst timescale, the directions of minimum magnetic field variations are perpendicular to the main flow and the background magnetic field directions.…”
Section: Comparison With Plasma Flow Datamentioning
confidence: 99%